2016
DOI: 10.1007/s10457-016-9976-1
|View full text |Cite
|
Sign up to set email alerts
|

Multitier agroforestry system for integrated resource conservation on uplands of Eastern Ghats region in India

Abstract: Soil and water conservation along with crop productivity improvement is indispensable for sustainable development of rainfed areas. Integration of suitable fruit trees within the cropping system can reduce risk allied with rainfed farming. The system of raising multi-height plant species with agricultural crops known as multitier agroforestry system was assessed (2007)(2008)(2009)(2010) for resource conservation and production potential in rainfed conditions of Eastern Ghats region in India. Thirty experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Jakhar et al [3] found that papaya + ginger : pigeonpea (8 : 2) + gliricidia system resulted in maximum net return, while in case of B : C ratio sole pigeonpea recorded maximum. Sankaranarayanana et al [10] noted that cotton + radish + cluster bean + beet root system gave maximum net return and per day profitability.…”
Section: Economics As Influenced By Multilayer Farmingmentioning
confidence: 99%
See 1 more Smart Citation
“…Jakhar et al [3] found that papaya + ginger : pigeonpea (8 : 2) + gliricidia system resulted in maximum net return, while in case of B : C ratio sole pigeonpea recorded maximum. Sankaranarayanana et al [10] noted that cotton + radish + cluster bean + beet root system gave maximum net return and per day profitability.…”
Section: Economics As Influenced By Multilayer Farmingmentioning
confidence: 99%
“…Jakhar et al [3] noted that papaya + ragi : pigeonpea (6 : 2) + gliricidia system recorded significantly lower water runoff, in addition to that papaya + ginger : pigeonpea (8 : 2) + gliricidia system found significantly lower soil erosion. Jakhar et al [3] reported that papaya + ginger + gliricidia multilayer system resulted better infiltration rate as compare to other system. Sultana et al [4] revealed that multilayer farming model of bitter gourd + elephant foot yam resulted in higher land equivalent ratio of system.…”
Section: Effect Of Multilayer Farming On Resource Conservationmentioning
confidence: 99%
“…About 13.15, 27.69, and 25.07% higher available N, P, and K were observed under LCP land use as compared to LCC land use in 2021 due to the continuous decomposition of forest litter applied as mulch in addition to leaf litter produced during fruit harvesting and litter fall under high moisture content present in the soil, which could help in a nutrient buildup in 26 years (Figure 5). When compared to traditional farmers' practices of growing finger millet, a mixed plantation of Moringa oleifera, Gliricidia sepium, Zingiber officinale, and Cajanus cajan with conservation measures in East India increased SOC, P, and K by 74%, 64%, and 66%, respectively (Jakhar et al, 2017). Litchi cultivation under conservation practices imparted good quality production of fruits and crops with higher productivity, ultimately leading to achieving the SDG of zero hunger and no poverty.…”
Section: Soil Enzyme Microbial Density Soil Microbial Biomass Carbon ...mentioning
confidence: 99%